A health impact assessment (HIA) on a new motorway bypass in Strasbourg, France. (30th September 2020) - Christie, D; Dardier, G; Jabot, F; Roué-LeGall, A; Cantoreggi, N; Mallet, Y; Tabbone, L; Simos, J
Abstract: Issue: In 2018-2019, HIA was carried out on a projected 24-km north-south motorway bypass in a rural area west of Strasbourg, intended to alleviate pressure on a pre-existing motorway that cuts through the city centre. Although transport is a major source of impacts on health, HIA is rarely performed on new road construction projects, globally. Description: The HIA included the screening, scoping, assessment and recommendations phases. Assessed health determinants were outdoor air quality, noise, mobility/access to health services, road safety, urban planning and the living environment. Methods included a literature review, the AirQ+ air pollution model, cartography and an NVivo analysis of answers to a public enquiry. Results: Noise was set to increase for 1-4% of the population in the study area, but impacts related to air pollution appeared to be negligible and road safety did not change substantially. Mobility and access to health services were to improve, with strong local differences (inequalities): some areas benefitted from access to the new motorway without being affected by noise or traffic, while for others it was the opposite. Stakeholders who participated in the public enquiry were concerned about the loss of agriculturally and environmentally valuable land, viewed as a collective cultural asset. Those living in the vicinity of the bypass expressed anger at the reduction of the quantity and quality of green areas, which was experienced as an injustice given their choice to live in a rural area. Our recommendations related mainly to the pre-existing urban motorway, where reducing traffic volumes and speeds, as well as diverting trucks onto the new bypass, had the most promising effects on health. Lessons: Due to its rural localization, the new road had limited health effects through air pollution, which is the focus of many transport-related HIAs. Through the analysis of the public enquiry, the HIA showed that the project generated anger and distress. Key messages: The substantial investment represented by the new bypass did not solve pre-existing problems related to environmental health but generated new ones linked to social and mental health issues. Many HIAs miss out on valuable qualitative information because interviews or focus groups cannot be carried out with local stakeholders. Secondary analysis of public consultations can fill this gap.